1975
DOI: 10.1159/000193649
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution of Pulmonary Blood Flow in Normal High-Altitude Dwellers at 3,650 m (12,200 ft)

Abstract: Simultaneous isotope dilution curves were recorded from the right upper (QRUZ) and right lower lung zones (QRLZ) by surface scanning in the sitting and recumbent positions in 15 normal high-altitude-born (HAD) males and in 1 HAD female as well as from 3 male newcomers, using 10 µCi of 131I-HSA as a bolus injection into the right ventricle. Similar information was also obtained at sea level from 5 normal males. The mean percent distribution of total pulmonary blood flow (Q) to RUZ and RLZ in the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Simultaneous isotope di lution curves, derived from these lung zones by surface scanning in the sitting and re-cumbcnt postures, revealed in male HAD a distribution of about 17% of cardiac output (0 ) to RUZ sitting contrasted with 26.0% in recumbeny. This is almost identical with the flow distribution to RUZ in sitting sealevel males [1] and appears to be uninflu enced by the elevation in mean pulmonary artery pressure (MPAP) of 7.7 mm Hg at La Paz above that extent at sea level.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Simultaneous isotope di lution curves, derived from these lung zones by surface scanning in the sitting and re-cumbcnt postures, revealed in male HAD a distribution of about 17% of cardiac output (0 ) to RUZ sitting contrasted with 26.0% in recumbeny. This is almost identical with the flow distribution to RUZ in sitting sealevel males [1] and appears to be uninflu enced by the elevation in mean pulmonary artery pressure (MPAP) of 7.7 mm Hg at La Paz above that extent at sea level.…”
supporting
confidence: 60%
“…The distribution of pulmonary blood flow was studied in accordance with the methods already detailed [1,2] and involved right heart catheteri zation. This was performed at the Cardio-Pulmo-nary Laboratory of the Instituto Boliviano de Biologia de Altura (IBBA) located at the Instituto Na tional de Torax, La Paz, Bolivia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning D dimer, an average of 320 ug/L was obtained in the Egyptian study [23] and 434 ug/L in the Indian study by Yanamandra [30], values well below those found in Huancayo where the average D dimer was 1295 ug/L in mild cases. The Egyptian study's patients with severe tomographic pulmonary compromise had an average D-dimer of 1210 ug/L.…”
Section: Discussionmentioning
confidence: 59%
“…This pattern of lower lobes compromise is consistent with the results reported by Malbuisson et al of the CT Scan ARDS Study Group [22], which found that the lower lobes received the greater pressure exerted by the heart and that that increased pressure was even greater in patients with ARDS as compared with normal controls. It is important to note that according to Coudert et al [23], in a study performed in La Paz, Bolivia, at high altitude, in healthy volunteers placed in the recumbent position, pulmonary artery flow was higher in the right lower lobe while lower in the right upper lobe.…”
Section: Discussionmentioning
confidence: 90%